2008
DOI: 10.1262/jrd.20031
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Nerve Growth Factor and its Receptors trkA and p75 and Inhibin .ALPHA.-Subunit in the Ovarian Interstitial Cells of Lactating Golden Hamsters

Abstract: Abstract. Characteristic daily increases in the plasma levels of luteinizing hormone (LH) are present every afternoon during lactation in golden hamsters. The objective of this study was to investigate the effect of the diurnal rhythm of increases in LH on expression of nerve growth factor (NGF), its receptors trkA and p75 and inhibin α-subunit in the ovarian interstitial cells of lactating golden hamsters. Both lactating and non-lactating groups of postpartum golden hamsters were used in this study. The expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Studies in golden hamsters have shown that NGF and its two receptors trkA and p75 are present in the ovary and uterus, demonstrating that NGF and its receptors trkA and p75 have important autocrine and paracrine regulatory roles in ovarian and oviductal function and uterine growth and proliferation during the estrous cycle [21,[32][33][34]. In our previous studies, NGF and its two receptors trkA and p75 were observed in numerous interstitial and luteal cells of golden hamsters [32].…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Studies in golden hamsters have shown that NGF and its two receptors trkA and p75 are present in the ovary and uterus, demonstrating that NGF and its receptors trkA and p75 have important autocrine and paracrine regulatory roles in ovarian and oviductal function and uterine growth and proliferation during the estrous cycle [21,[32][33][34]. In our previous studies, NGF and its two receptors trkA and p75 were observed in numerous interstitial and luteal cells of golden hamsters [32].…”
mentioning
confidence: 76%
“…Inhibin production is restricted mainly to steroidogenic tissues and the hypophysis, whereas activins are produced in many cell types and organs [24][25][26]. It is now clear that inhibin/activin subunits could exert local autocrine and paracrine roles on steroidogenesis and folliculogenesis within developing ovaries [27][28][29][30][31].Studies in golden hamsters have shown that NGF and its two receptors trkA and p75 are present in the ovary and uterus, demonstrating that NGF and its receptors trkA and p75 have important autocrine and paracrine regulatory roles in ovarian and oviductal function and uterine growth and proliferation during the estrous cycle [21,[32][33][34]. In our previous studies, NGF and its two receptors trkA and p75 were observed in numerous interstitial and luteal cells of golden hamsters [32].…”
mentioning
confidence: 99%
“…NGF and its receptors, under the influence of gonadotropins and/or ovarian hormones, play a crucial regulatory role in these processes. 32-34 The roles of NGF and its receptors in ovary of the wild ground squirrel have been studied, indicating in situ synthesis and secretion of NGF and its receptors in ovaries of the wild ground squirrel, where the role of NGF might be mediated via both receptors TrkA and P75 to affect follicular development. 25 Moreover, the expression levels of NGF and its receptors, TrkA and p75, were significantly higher in the breeding season compared to the nonbreeding season, suggesting that the NGF system may be involved in the regulation of ovarian function changes.…”
Section: Discussionmentioning
confidence: 99%
“…NGF and its receptors, under the influence of gonadotropins and/or ovarian hormones, may play a crucial regulatory role in these processes. The roles of NGF and its receptors in the ovary, uterus, and ovarian interstitial cells of golden hamsters have been studied, and these roles and the modulation of expression of NGF and its receptors differs among the various reproductive tissues [21,22,26]. In the ovarian tissues of golden hamsters, immunopositive reactions of NGF and its receptors were found in oocytes, theca and granulosa cells of different sized follicles [22].…”
mentioning
confidence: 99%
“…Positive reactions for NGF and its receptors were also present in interstitial cells during the estrous cycle. Furthermore, the LH surge may be an important factor for stimulating the production of NGF and its two receptors in the interstitial cells of the golden hamster [26]. NGF and its two receptors are present in uteri of golden hamsters and their expression is stimulated by estrogen and progesterone [21].…”
mentioning
confidence: 99%